Multicriteria assessment of water dynamics reveals subcatchment variability in a seemingly homogeneous tropical cloud forest catchment. Issue 7 (28th February 2017) - Timbe, Edison; Feyen, Jan; Timbe, Luis; Crespo, Patricio; Célleri, Rolando; Windhorst, David; Frede, Hans‐Georg; Breuer, Lutz
Abstract: To improve the current knowledge of the rainfall–runoff phenomena of tropical montane catchments, we explored the usefulness of several hydrological indicators on a nested cloud forest catchment (76.9 km 2 ). The used metrics belong to 5 categories: baseflow mean transit time, physicochemical properties of stream water, land cover, topographic, and hydrometric parameters. We applied diverse statistical techniques for data analysis and to contrast findings. Multiple regression analysis showed that mean transit times of base flow could be efficiently predicted by sodium concentrations (higher during baseflows) and temperatures of stream water, indicating a major influence of geomorphology rather than topographic or land cover characteristics. Principal component analysis revealed that no specific subset of catchment indicators could be identified as prevailing descriptors for all catchments. The agglomerative hierarchical clustering analysis provided concomitant results, implying larger levels of dissimilarity between smaller subcatchments than between larger ones. Overall, results point out an intricate interdependence of diverse processes at surface and subsurface level indicating a high level of heterogeneity. Disregarding heterogeneity of nested or paired catchments could lead to incomplete or misleading conclusions, especially in tropical mountain regions where pronounced spatial and temporal gradients are present.